An experimental study and model development of poly(ethylene terephthalate) yarn morphology - Yıldırım, Kenan; Ulcay, Yusuf (Walter De Gruyter Gmbh, 2014)
In this study, macromolecular arrangements in fibers were investigated and a novel approach based on model development for partially oriented (POY) polyethylene terephthalate (PET) yarn morphology was proposed. Differential scanning calorimeter (DSC) analysis, Fourier transform infrared (FT-IR) analysis, boiling water shrinkage and tensile tests were performed through the study. DSC thermogram, FT-IR spectra, stress-strain curve, the change in the boiling water shrinkage properties and data from the literature were used to develop the model for POY PET fiber morphology. In order to make a comparison, textured PET yarn morphology was also investigated. The neck formations during tensile tests, cold crystallization on the DSC thermogram, peak formation on the FT-IR spectrum of the POY PET yarn after texturizing and shrinkage test at 971 and 845 cm(-1) and shrinkage phenomenon have been explained by this model.
Keywords: model for POY fiber structure; morphology; PET yarn; stress-strain curve; thermal behavior